The masjid as a restorative environment: a case study of Masjid Sultan Ahmad Shah, IIUM - Nor Rahim, Mohd Norhafifi; Mohamad Ramsi, Alya Qaryna; Mohd Nor, Aliaa Nabila; Mohd Tamsir, Nur Nasyitah Syahrain; Mohd Mahudin, Nor Diana (Kulliyyah of Architecture and Environmental Design, IIUM, 2013)
While studies have been conducted on the restorative effects of monasteries and churches, limited research is available that investigates the restorative effects of a masjid or mosque. This study therefore focuses on the restorative effects that the Sultan Haji Ahmad Shah (SHAS) Masjid in IIUM has on its visitors. The study aims to answer four research questions namely, gender differences in the motivation of Masjid goers, areas of the Masjid that bring the most restorative effects, the restorative effects of the Masjid on mood outcome, and the relationship between motivation, activities, and mood of Masjid visitors. Analyses demonstrate four important results: (1) there is no statistically significant difference in gender on motivation for going to the Masjid; (2) the areas of the Masjid that give most restorative effect vary; (3) restorative effects are observed in terms of improvement in mood after visiting the Masjid; and (4) there is a significant relationship between the motivation, engaged activities, and the mood outcome among Masjid goers. Altogether, the results suggest that Masjid has restorative potential for enhancing spiritual needs as well as inducing positive changes in mood among its visitors.